(untitled) (Dhaka University Journal of Biological Sciences, 2026)
This cross-sectional pilot study examined depression and anxiety disparities among Bangladeshi Secondary School Certificate (S.S.C.) examinees during COVID-19. Two secondary schools were selected by feasibility/administrative access (one urban, one rural; from Dhaka and Rangpur), and 195 students (Mage = 14.79 years, SD = 0.92 years; 158 female, 37 male) completed the Beck Depression Inventory for Youth (BDI-Y) and the Beck Anxiety Inventory for Youth (BAI-Y). Urban students reported significantly higher depression (ΔM = 6.93, p < .001, q < .05, d = .64) and anxiety (ΔM = 3.59, p = .012, q = .024, d = .38) than rural peers. Females exhibited significantly greater anxiety than males (ΔM = 4.29, p = .017, q = .023, d = .44). No significant difference was observed in depression scores between males and females (p = .07, q = .07, d = 0.38). Findings of the pilot indicate elevated scores of anxiety and depression across subgroups and may inform school-based supports, with attention to urban contexts and gender-responsive approaches. Dhaka Univ. J. Biol. Sci. 35(1): 83-93, 2026 (January)